1998
DOI: 10.1016/s0895-7061(98)00141-1
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive therapy and insulin sensitivity: Do we have to redefine the role of β-blocking agents?

Abstract: Essential hypertension is, at least in many subjects, associated with a decrease in insulin sensitivity, whereas glycemic control is (still) normal. Metaanalyses of hypertension intervention studies revealed different efficacy of treatment on cerebral (cerebrovascular accidents [CVA]) and cardiac (coronary heart disease [CHD]) morbidity and mortality. Although CVA were reduced to an extent similar to that anticipated, the decrease in CHD was less than expected. These differences are likely to be caused by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
112
1
8

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(124 citation statements)
references
References 36 publications
3
112
1
8
Order By: Relevance
“…In addition, it improved glucose sensitivity. These data confirmed previous observations in humans and experimental animals without renal disease that showed that RAS blockers are able to ameliorate the metabolic adverse effects that are observed in MS (33)(34)(35)(36)(37)(38). However, to our knowledge, this is the first study to analyze the effect of ARB on IR that is associated with kidney disease.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, it improved glucose sensitivity. These data confirmed previous observations in humans and experimental animals without renal disease that showed that RAS blockers are able to ameliorate the metabolic adverse effects that are observed in MS (33)(34)(35)(36)(37)(38). However, to our knowledge, this is the first study to analyze the effect of ARB on IR that is associated with kidney disease.…”
Section: Discussionsupporting
confidence: 90%
“…Besides changes in hemodynamic forces, additional mechanisms could be involved in the beneficial effects of olmesartan on IR because not all of the antihypertensive drugs ameliorate insulin sensitivity (35,36): In fact, ␣ blockers, ACEI, and angiotensin II receptors antagonists are the ones that have been shown to improve it. By contrast, diuretics and ␤ blockers worsen insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…b-blockers may cause impaired lipid and glucose metabolism and should not be used as first choice therapy in obese hypertensive patients unless required by specific indications. 86,87 However, these effects seem to be less pronounced with the new vasodilating b-blockers such as carvedilol and nebivolol. 88 First choice drugs for the obesity-induced hypertension are the Ang receptor antagonists and the ACE-inhibitors both associated with a lower incidence of diabetes 85 and favorable effects on left ventricular hypertrophy and nephropathy.…”
Section: Endothelial Dysfunction and Changes In Vascular Structurementioning
confidence: 99%
“…At the same time, according to the purpose of the analysis Jasob et al (1998), which combines a number of studies on treatment of hypertension with the use of beta-blockers, it appears that some of them may even increase the sensitivity of peripheral tissues to insulin [6].…”
Section: Discussionmentioning
confidence: 99%